Development of a low-pass filter for partial discharge testing system with the power frequency converter - Prombud, T.; Kitcharoen, P.; Yutthagowith, P. (My University, 2018)
The development of a low-pass filter for partial discharge test system that based on a power frequency converter is presented in this paper. The PD testing system is composed a 200-Hz power frequency converter and the designed filter connected with a high-voltage test transformer and a conventional partial discharge detection system. It is found that the power frequency converter acting as the low-voltage source always provides the high noise level with effecting to the background noise occur in the partial discharge test. Sometimes noise level is higher than the acceptable level of the PD tests in some high-voltage equipment such as potential transformers, distribution transformer, and so on. In this paper, the performances of the filters with different designs are studied and compared the result in terms of the output voltage difference (RMS, voltage , and ,peak,voltage 2), total harmonic distortion of the output high voltages value (THDv), and value of background noises as occur in the partial discharge test. The low-voltage source based on uni-polar pulse width modulation (PWM) topology was employed in the PD testing system. From the experimental results, the designed filter shows the promising performances with low levels of the background noise, THDv, and voltage difference. The experimental results show that the background noise is lower than 2.0 pC, the voltage difference and THDv are less than 5%. In addition, the designed filter has been tested in the partial test of a real potential transformer successfully.
Keywords: frequency converter; high-voltage tests; low-pass filter; partial discharge; potential transformer